Glasdtone and Disraeli - Michael J Lynch (Hodder and Stoughton, 1991)
The aims of this book are provide a set of key documents illustrating the careers of Glasdtone and Disraeli and to suggest, by a series of questions and sample answers, how the source material can best be analysed and interpreted